Efektivitas Esktrak Akar Kenikir (Cosmos caudatus Kunth) dan Pepaya (Carica papaya L) dalam Menekan Terbentuknya Puru Akar Nematoda pada Tanaman Seledri (Apium graveolensL) - Asty, Nur; Siahaya, Victor G; Umasangaji, Aminudin (Jurnal Agrosilvopasture-Tech, 2023)
This study aims to test the effectiveness of root extracts of kenikir and papaya plants in suppressing the rate of root-knots formation, as well as the number of root-knots formed on celery plants. The method used was a factorial experiment in a randomized block design with two factors, namely the type of antagonist plant root and the dosage, with five replications. The results showed that the treatment of papaya root extract (Carica papaya L.) had a significant effect on all parameters, but the HSD test was only significantly different on the number of root knots. The highest average number of root knots in control plants was 67.2 (A1B0), and the lowest was 4.6 (A1B5). The treatment of kenikir root extract (Cosmos caudatus Kunth.) significantly affected all parameters, but the HSD test was only significantly different on plant height and number of root knots. The average plant height in the control was 31.4 cm (A2B0), and in the treatment 40.6 cm (A2B5). The highest average number of root knoots was 50.8 (A2B0), and the lowest was 1.0 (A2B5). Carpain secondary metabolites in papaya root extract, and phenylpropanoids in kenikir root extract played a role in suppressing the growth of root-knot nematodes. Coniferyl alcohol in kenikir root extract is thought to play a role in increasing the height of celery plants. Kenikir root extract was better than papaya root extract in suppressing the growth of root-knot nematodes.